GPU-Based DEM Simulations of Global Ice Resistance on Ship Hull During Navigation in Level Ice - Hu, Bing; Liu, Lu; Wang, De-yu; Ji, Shun-ying (China ocean engineering, 2021)
The ice resistance on a ship hull affects the safety of the hull structure and the ship maneuvering performance in ice-covered regions. In this paper, the discrete element method (DEM) is adopted to simulate the interaction between level ice and ship hull. The level ice is modeled with 3D bonded spherical elements considering the buoyancy and drag force of the water. The parallel bonding approach and the de-bonding criterion are adopted to model the freezing and breakage of level ice. The ship hull is constructed with rigid triangle elements. To improve computational efficiency, the GPU-based parallel computational algorithm was developed for the DEM simulations. During the interaction between the ship hull and level ice, the ice cover is broken into small blocks when the inter-particle stress approaches the bonding strength. The global ice resistance on the hull is calculated through the contacts between ice elements and hull elements during the navigation process. The influences of the ice thickness and navigation speed on the dynamic ice force are analyzed considering the breakage mechanism of ice cover. The Lindqvist and Riska formulas for the determination of ice resistance on ship hull are employed to validate the DEM simulation. The comparison of results of DEM, Lindqvist, and Riska formula show that the DEM result is between those the Lindqvist formula and Riska formula. Therefore the proposed DEM is an effective approach to determine the ice resistance on the ship hull. This work can be aided in the hull structure design and the navigation operation in ice-covered fields.